Community of protozoans and metazoans parasitizing Auchenipterus nuchalis (Auchenipteridae), a catfish from the Brazilian Amazon (Acta Scientiarum. Biological Sciences, 2017)
This paper describes the first study on parasite diversity in Auchenipterus nuchalis Spix & Agassiz, 1829 (Auchenipteridae). In 31 fish caught in a tributary of the Amazon River, 10,708 parasites were collected, such as Ichthyophthirius multifiliis, Piscinoodinium pilullare, Cosmetocleithrum striatuli, metacercariae of Posthodiplostomum sp, and larvae and adults of Procamallanus (Spirocamallanus) inopinatus. These parasite species showed aggregated dispersion, except for C. striatuli, which had a uniform dispersion. The component community of parasites showed a low Brillouin diversity (0.67 ± 0.27), low species richness (3.5 ± 0.8) and low evenness (0.43 ± 0.17), and it was characterized by the presence of species with high prevalence and abundance. Protozoan species were the prevalent parasites, which may be a consequence of the host’s mode of life, while the low presence of endoparasites in A. nuchalis suggests that this fish may occupy an intermediate trophic level in the food web. These data represent the first record of such parasite species for this host.